Type designations for Centaurea saxicola and Cirsium valentinum (Asteraceae) - Ferrer-Gallego, P. Pablo (Phytotaxa, 2024)
Nomenclatural types of the names Centaurea saxicola and Cirsium valentinum are discussed. A specimen collected by Ángel Guirao in 1852 in Orihuela (Alicante province, Spain) and preserved at P is designated as the neotype of C. saxicola. A specimen preserved at E and collected by Porta and Rigo in 1891 in Valencian Community (Spain) is designated as the second-step lectotype of C. valentinum.